Helically-coiled-wire-induced swirl flow heat transfer and pressure drop in a circular tube under velocities controlled. (1st May 2023) - Hata, K.; Shibahara, M.
Highlights: Employed a SUS304 circular test tube with the helically-coiled-wire insert. Investigated helically-coiled-wire-induced swirl flow heat transfer. Solved RANS equations for a k–ε turbulence model on a circular tube with the helically-coiled-wire insert. Measured the thickness of conductive sub-layer and non-dimensional thickness of conductive sub-layer for the turbulent heat transfer on a circular tube with the helically-coiled-wire. Derived the correlations of Nusselt number, conductive sub-layer and non-dimensional thickness of conductive sub-layer for helically-coiled-wire-induced swirl flow heat transfer in a vertical circular tube. Abstract: Systematic measurements of the swirl flow heat transfer by the helical coil-wire and the pressure drop across the helical coil-wire were made by the experimental water loop flow with exponentially increasing heat input at mass velocities G = 3928 to 13, 496 kg/m 2 s, inlet liquid temperatures Tin =284.14 to 307.57 K and inlet pressures Pin =763.80 to 1027.85 kPa. Systematic measurements of the pressure drop across the helical coil-wire were performed without heating circular tube. The measurements were performed on the inner surface of a SUS304 circular test tube with an inner diameter of 6 mm, a heated length of 59.7 mm, and a thickness of 0.5 mm, in which a helical coil was inserted. SUS304 helical coiled wire with wire diameter dw =2.025 mm, coil diameter Dc =3.4917 mm, total length l = 370 mm, coil pitch 360° rotation pc =37.222 mm, and coil pitch ratio yc = pc /d = 6.204 was employed. The relationship between swirl velocity and pump input frequency and that between fanning friction factor and Reynolds number ( Red =1.949 × 10 4 to 1.274 × 10 5 ) were clarified beforehand. On the other hand, the RANS (Reynolds mean Navier-Stokes simulation) equations for the k-ε turbulence model in a circular tube of 6 mm diameter and 626 mm length with helical coil inserted, considering the temperature dependence of the thermophysical properties concerned, were numerically solved for the heating of water on a heated section of 6 mm diameter and 60 mm length under the same conditions as the experiment by using the PHOENICS code. The helical coiled wire of dw =2.025 mm, Dc =3.4917 mm, l = 370 mm, pc =37.222 mm and yc =6.204 was installed at the same experimental location. The surface heat fluxes q and average surface temperatures Ts, av on a circular tube with a helical coil of yc =6.204 obtained theoretically were compared with the corresponding experimental values on the graph of q versus temperature difference between average heater inner surface temperature and liquid bulk mean temperature ΔTL [= Ts, av -TL, TL =( Tin + Tout )/2]. The numerical solutions for q and ΔTL were almost identical to the corresponding experimental values for q and ΔTL, with deviations from 0 to +20% for the ΔTL range tested here. The numerical solutions of the local surface temperature (Ts )z, the local average liquid temperature (Tf, av )z, and the local liquid pressure drop ΔPz were also compared with the corresponding experimental values of (Ts )z, (Tf, av )z, and ΔPz against heated length L or distance from the test section inlet Z, respectively. The numerical solutions of (Ts )z, (Tf, av )z and ΔPz differ from the corresponding experimental data of (Ts )z, (Tf, av )z and ΔPz within ± 5%. The thickness of the conductive sublayer δCSL [= (Δr)out /2 ] and non-dimensional thickness of the conductive sublayer y + CSL [=(fF /2) 0.5 ρl usw, c δCSL /μl ] for turbulent heat transfer on a circular tube with helical coiled wire are clarified on the basis of numerical solutions in the swirl velocity usw, c ranging from 5.108 to 17.146 m/s. Correlations of Nusselt number Nud, δCSL, and y + CSL for the swirl flow heat transfer in a vertical circular tube with helical coil wire are also derived.